The Matter of Grandma Minah in the Perspective of Positivism - YAPRIZAL, Andi; THEOPILUS, Ebith; KRISTHY, Mutia Evi (Indonesia Strategic Sustainability, 2023)
Purpose: In a law there are various parties who will enforce the laws in force in Indonesia. These parties carry out law enforcement so as not to create a violation of the law, bring order to society and regulate society in accordance with the norms and rules that apply in a country is not easy to apply in public life.Methodology:The resolution of a case of violation of the law is a legal process. Legal process is an action to resolve cases of violations of the law to achieve a settlement in accordance with applicable regulations in Indonesia.Findings: In legal cases that have occurred in Indonesia, the provision of criminal sanctions against Grandma Minah who is a cocoa thief has received a lot of attention from the public. The case of